Malaria Mapping Based on Epidemiological Variables in Bobonaro and Covalima Districts, Timor Leste - Gusmao, Francelino Nobel Sarmento; Adu, Apris A.; Dwi Wahyuni, Maria Magdalena; Ruliati, Luh Putu; Manurung, Imelda F.E. (Ann Publisher, 2025)
Background. Malaria is an infectious disease caused by Plasmodium parasites and transmitted through the bite of infected female Anopheles mosquitoes. According to the Ministry of Health of Timor-Leste's 2023 malaria elimination report, Covalima, Bobonaro, and Oecuse districts collectively reported 9 malaria cases in 2023, along with a notable vector density. Spatial analysis offers a comprehensive method for compiling and managing spatial data, transforming it into meaningful insights. Aims. This study aims to describe malaria mapping based on epidemiological variables in Bobonaro and Covalima Districts, Timor-Leste. Methods. This descriptive epidemiological research utilizes malaria case reports from Bobonaro and Covalima Districts as its population and sample. Result. The results indicate that the Annual Malaria Incidence (AMI) and Annual Parasite Index (API) in these districts showed an increasing trend from 2019-2023, mainly attributable to imported cases from the border region between Covalima and Malaka Districts. Males and individuals over 15 years of age are more frequently affected by malaria, likely due to their higher levels of mobilization for work or other activities. Plasmodium falciparum is the most common species identified, primarily associated with swamp habitats. Conclusion. Covalima District has two temporary and one permanent swamp. Additionally, lake and lagoon habitats were identified in the Covalima Regency. The two regencies share similar conditions regarding sun intensity, rainfall, temperature, humidity, and altitude. Implication. Communities can play a crucial role in independent malaria vector control efforts, such as introducing larvivorous fish into water bodies and eliminating stagnant water puddles around homes